(untitled) (The Review of Diabetic Studies, 2025)
Background: Pediatric central nervous system (CNS) tumor surgery is associated with significant postoperative morbidity, including renal complications. The kidneys are vulnerable to perioperative hemodynamic changes, nephrotoxic drug exposure, and metabolic stress. This study aimed to assess the incidence, risk factors, and outcomes of renal complications in children following CNS tumor surgery. Methods: A retrospective observational study was conducted on 120 pediatric patients (aged 0–18 years) who underwent surgical intervention for CNS tumors. Data on demographics, tumor characteristics, perioperative factors, and renal function were collected from medical records. Renal complications, primarily acute kidney injury (AKI), were defined using established pediatric criteria. Statistical analyses were performed to identify associations between perioperative factors and renal outcomes. Results: Postoperative renal complications occurred in 25% of patients, with AKI being the most common (20.8%). The majority of AKI cases were stage 1 (48%), while 20% were severe (stage 3), and 4.2% of all patients required dialysis. Significant risk factors for renal complications included prolonged surgery duration (>5 hours) (p=0.01), intraoperative hypotension (p=0.03), and exposure to nephrotoxic drugs (p=0.04). Younger age (<5 years) showed a trend toward higher risk but was not statistically significant. Conclusion: Renal complications, particularly AKI, are common in pediatric patients after CNS tumor surgery, affecting one-quarter of the cohort. The identified risk factors highlight the need for vigilant perioperative monitoring, optimized hemodynamic management, and judicious use of nephrotoxic agents. A multidisciplinary approach is essential to mitigate renal injury and improve both short-term and long-term renal outcomes in this vulnerable population.